Derailment Assessment using FBG - Kumar, Ajit (International Journal of Computer Sciences and Engineering, 2014)
This paper proposes the use of FBG sensor to measure the lateral and vertical forces at the flange contact point. The ratio of lateral and vertical force at the rail-wheel contact point is called Nadal limit for a certain critical value which decides the derailment. Simulation has been done for the measurement of lateral and vertical forces with the increasing velocity and taking the range of radius of curvature from 600m to 1000m.